Estimating apparent survival of sub-adult and adult white sharks (Carcharodon carcharias) in central California using mark-recapture methods - Kanive, Paul E.; Rotella, Jay J.; Jorgensen, Salvador J.; Chapple, Taylor K.; Anderson, Scot D.; Klimley, A. Peter; Block, Barbara A. (Frontiers in Marine Science, 2015)
Quantifying life history parameters of marine top predators such as sharks is challenging, as observations are difficult. However, these parameters are critical for accurate population assessments and understanding of population dynamics. Using mark recapture observations at white shark foraging aggregation sites, we tested for differences in survival between sexes and estimated apparent survival for sub-adult and adult white sharks in neritic waters off central California. We used six years of mark-recapture data and a model that accounted for imperfect detection and imperfect sex assignment. Empirical information based on direct observations suggests that there are no sex-specific or temporal differences in survival during the study period and that survival was estimated to be 0.90; SE = 0.04. Additionally, after animals whose sex was unknown throughout the study period were probabilistically assigned to sex, the ratio in this sample is estimated to be 2.1 males for every female observed. This estimated ratio is lower than the observed ratio of 3:1. We demonstrate that the estimated capture probability for males was roughly twice as high as that for females (0.41, SE = 0.06 and 0.19, SE = 0.07 respectively). Together these results suggest (1) that the sex ratio is uneven but not as skewed as uncorrected observation data would suggest and (2) that unequal mortality in older age classes are not the cause of the observed sex bias but more likely results from disparate mortality earlier in life or differences in behavior. Future research is needed to explore the potential causes of the observed sex bias.